Mapping and Candidate Gene Identification for Adult Plant Resistance to Stripe Rust in the Chinese Wheat Landrace Laohongmai - Xu, Xiaowei; Feng, Jing; Wang, Fengtao; Shah, Syed J A; Lin, Ruiming (Plant disease, 2025)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most devastating diseases affecting wheat production worldwide. Wheat resistant cultivars can effectively prevent and limit the occurrence and spread of the disease. Chinese wheat landrace Laohongmai (LHM) demonstrated a high level of resistance to stripe rust at the adult plant stage. To identify and map loci associated with resistance to stripe rust in LHM, a total of 224 recombinant inbred lines (RILs) were developed by crossing LHM with Taichung 29. Maximum disease severity was assessed for the parents and RILs in the fields inoculated with currently prevalent Pst races in Langfang, Hebei in 2023 and 2024 and in Chengdu, Sichuan in 2024. The wheat 55K SNP array was used to genotype the RILs. A new major adult plant resistance locus, QYr.LHM-1AL, was identified and mapped to a genetic interval of 3.51 cM between markers 45KASP1A-4 and 45SSR1A-973 on the long arm of chromosome 1AL corresponding to a 553.9 to 554.0 Mb region in the Chinese Spring reference genome. The genome region contains four genes, including TraesCS1A01G383100 encoding cysteine peptidase. The gene was found to be involved in responding to Pst invasion as confirmed by a qRT-PCR analysis. Among 50 wheat landraces tested with the three linked markers, 3 landraces had the Laohongmai haplotype. The markers are useful in molecular breeding.